Transcutaneous Auricular Vagus Nerve Stimulation Differently Modifies Functional Brain Networks of Subjects With Different Epilepsy Types - von Wrede, Randi; Rings, Thorsten; Bröhl, Timo; Pukropski, Jan; Schach, Sophia; Helmstaedter, Christoph; Lehnertz, Klaus (Frontiers in Human Neuroscience, 2022)
Epilepsy types differ by pathophysiology and prognosis. Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive treatment option in epilepsy, however, its way of action and impact on different types of epilepsy are still unknown. We investigated whether short-term taVNS differently affects local and global characteristics of EEG-derived functional brain networks in different types of epilepsy. Thirty subjects (nine with focal epilepsy, 11 with generalized epilepsy, and ten without epilepsy or seizures) underwent a three-hour continuous EEG-recording (one-hour pre-stimulation, one hour taVNS stimulation, one-hour post-stimulation) from which we derived evolving functional brain networks. We assessed – in a time-resolved manner – important global (topological, robustness, and stability properties) and local (centralities of vertices and edges) network characteristics. The study was accompanied by neuropsychological testing prior to and after the EEG-recording. Compared to the subjects with focal epilepsies and without epilepsy, those with generalized epilepsies clearly presented with different topological properties of their functional brain network already at rest. Furthermore, subjects with focal and generalized epilepsies reacted differently to the stimulation, expressed as different taVNS-induced immediate and enduring reorganization of global network characteristics. On the local network scale, no discernible spatial pattern could be detected, which points to a rather unspecific and generalized modification of brain activity. Assessing functional brain network characteristics can provide additional information for differentiating between focal and generalized epilepsy. TaVNS-related modifications of global network characteristics clearly differ between epilepsy types. Impact of such a non–pharmaceutical intervention on clinical decision-making in the treatment of different epilepsy types needs to be assessed in future studies.